2015
DOI: 10.3390/computation3020128
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation and Optimisation of a Low Energy Ventilation and Cooling System

Abstract: Mechanical Heating Ventilation and Air-Conditioning (HVAC) systems account for 60% of the total energy consumption of buildings. As a sector, buildings contributes about 40% of the total global energy demand. By using passive technology coupled with natural ventilation from wind towers, significant amounts of energy can be saved, reducing the emissions of greenhouse gases. In this study, the development of Computational Fluid Dynamics (CFD) analysis in aiding the development of wind towers was explored. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Therefore, it is essential to replace the mechanical systems with passive techniques known to have low energy consumption and carbon emissions and provide good indoor air quality [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to replace the mechanical systems with passive techniques known to have low energy consumption and carbon emissions and provide good indoor air quality [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The computational domain consisted of an inlet on one side of the domain, and an outlet on the opposing boundary wall with the thermal chair located centrally. Due to the complexity of the model, a non-uniform mesh was applied to volume and surfaces of the computational domain [50,51]. The generated computational mesh is shown in Figure 7.…”
Section: Computational Geometrymentioning
confidence: 99%
“…The review of current literature showed that significant research interest has been focused on a number of areas relating to the development of windcatcher technology [8][9][10][11][12][13][14][27][28][29][30] and its integration with cooling methods [23][24][25][26] such as heat pipes [15][16][17][18]. The research gaps that this study aims to address are the following; (1) There are limited studies on the experimental investigation of commercial windcatchers, particularly using field test method.…”
Section: Figurementioning
confidence: 99%
“…Several researchers [27][28][29][30] focused on the aerodynamics design and ventilation performance of wind towers and its components.…”
Section: Figurementioning
confidence: 99%